The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages A SHIPYARD WORKER. There is one interesting point that I should like to bring out. In the boilermaking trade conditions are very primitive indeed. The sanitary arrangements go back to the Middle Ages. I am glad that the Communist Party has organised this Conference and has shown us that something can be done to improve conditions. In my trade everyone knows that welding has come to play a big part. It is already one of the chief processes in America and it is rapidly becoming one in Britain. As a boilermaker I often work where welding is being carried on and I often suffer from what is known as "flash." By 11 o'clock at night I begin to feet something like grit in my eyes and I can't see. Also, the skin becomes very sore and begins to peel off. This is known as "ray burn." When you go to the Ambulance Room for attention you are fobbed off with a few drops in your eyes and the checker may take your name. Sometimes there is no notice taken of you at all and the result is that you may take a few days off to get over the effects. When you make complaints, the answer you get is that you are "soft." Here is a question for the Health and Welfare Committees which the Conference has spoken about. A FACTORY WORKER. What we should be doing here, is to prepare ourselves to take control of industry. Unfortunately, we have not done so. But I thing [think] it would be a step in the right direction if we would realise that it is the law now, that a factory with 250 workers must have a canteen. I think that a factory of 250 workers with its own canteen could easily support its own Welfare Officer. Miners have had their checkweighman for years, most factories have shop stewards and now many factories have their Joint Production Committees, why then cannot they have their own Welfare Officers. If we had such people who knew the rules and regulations, we would have taken an important step in the direction of workers' control in industry. BOB SMITH (Shipyard Worker). Shipyards are very queer places. Most of them are very old and sanitary conditions are abominable. One uses the toilet arrangements at the risk of one's life. This Conference has made it clear that many improvements can be made under the existing Board of Trade regulations and others from the Ministry of Health. We have some medical staff in the shipyards and some nursing personnel, too. In addition there is a visiting medical officer. But the visiting doctor is terribly overworked and has to see 40 odd cases in a two hour visit. Obviously he cannot give them any real attention. With regard to the boilermaker and welding. I pressed our management some time ago to provide free milk for the welders, because having worked in the Soviet Union, I knew that welders there were provided with both milk and eggs free. I thought our management might be friendly to the idea but I was mistaken. When I tried to interest the boilermakers themselves in the idea they thought it was being soft. 16 15X/2/103/295